Narrative and Dramatic Approaches to Children's Life Story with Foster, Adoptive and Kinship Families Using the 'Theatre of Attachment' Model. - Moore, Joan E. (London : Routledge, 2020)
Narrative and Dramatic Approaches to Children's Life Story with Foster, Adoptive and Kinship Families outlines narrative and dramatic approaches to improve vulnerable family relationships. It provides a model which offers new ways for parents to practise communicating with their children and develop positive relationships. The book focuses on the Theatre of Attachment model - a highly innovative approach which draws from a strong theoretical base to demonstrate the importance of narrative and dramatic play for sharing the children's life history in the family home with their adoptive, foster or kinship parents. An emphasis is on having fun ways to work through complex feelings and divided loyalties, so as to secure attachment. This practice model aims to raise children's self-esteem and communication skills and to combat the profound effects of abuse, neglect on trauma on children's development. This book will be of great interest for academics, post-graduate students, universities and Training bodies, service providers and practitioners involved in social work and creative therapies, child psychologists, child psychotherapists and public and private adoption and foster care agencies.
IntroductionIdentity; Developing a coherent narrative; Writing the life story; Delivering the life story; Stories of equivalent adversity; Life maps -- Case example: Luke, Alice and Robbie; Water game -- Case example: Mark and Sharron; Clay -- Case example: Louis; Costume drama -- Case example: Gemma; Candle ceremonies -- Case example: Pritti; Children's reactions to difficult truths -- Case example: Rowan; Reworking childhood -- Case example: Jay; Secrets -- Case example: Lucy; Betrayal -- Case example: Billy; Summary; 7 Finding a balance; Introduction; Conflicts; Case examples -- Case example: Pritti
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: FAMILY & RELATIONSHIPS / Adoption; FAMILY & RELATIONSHIPS / Parenting / General; PSYCHOLOGY / Psychotherapy / Child & Adolescent; Attachment behavior in children; Foster children -- Psychology; Adopted children -- Psychology